Investigation of a New Natural Cellulosic Fiber Extracted from Beetroot Plant. Issue 16 (28th November 2022) - Eyupoglu, Seyda; Eyupoglu, Can
ABSTRACT: The fundamental aim of this study is to acquaint a novel sustainable cellulosic fiber obtained from beetroot plant for using in composite and textile industries. Natural cellulosic beetroot fibers were extracted from beetroot plant with biological degradation method. In order to determine the fiber properties, chemical, physical, and instrumental tests were carried out for fibers. The surface of samples was scanned using a scanning electron microscope (SEM). The elemental composition of fibers was analyzed with an energy dispersive X-ray analysis (EDX) device. Crystallographic properties of fibers were determined with X-ray diffraction (XRD) technique. Thermal degradation behavior of fibers was investigated with thermogravimetric analysis. SEM analyses show that the fibers have a cylindrical morphology and a 284.04-µm diameter. EDX analysis revealed that the fibers have 52.39% carbon and 47.46% oxygen. The XRD analysis indicates that beetroot fiber contains crystallinity index (Crl) of 87% and crystallite size (L) of 3.92 nm. According to the TGA analysis, the major degradation of fibers occurs at a temperature range of 288.09°C to 358.54°C. Mechanical characteristic of fibers was detected with tensile test, which provided information about strength, elongation, Young's modules, and microfibril angle. The tensile strength, elongation, and Young's modules of fibers are 50.68 MPa, 7.72%, and 6.56 GPa, respectively. The results show that mechanical behaviors and chemical characteristics of beetroot fibers are compatible with other cellulosic fibers.